“Marta Riquelme”: when the absurd becomes the real (Anclajes, 2014)
The analysis of Ezequiel Martínez Estrada´s Around Kafka and other essays allows to recognize the concept of realism (inherited from the Czech author) that he manages in his narratives. In “Marta Riquelme,” one of his stories, he discursively constructs an image of “the other” upon different textual levels: author, narrator, genre, characters, etc. At the same time, Martinez Estrada manifests a feeling of foreignness in the production of his real and fictional contexts, that is, in the creation of particular texts. The findings show that this writer presents a personal image of “the different” when related to the conception of traditional narrative.
Keywords: Ezequiel Martínez Estrada; Argentina Literature; Literary Criticism; Twentieth Century; Argentina